The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1093/jme/tjv014
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Survey of Ectoparasites and Associated Pathogens from Norway Rats in New York City

Abstract: The Norway rat (Rattus norvegicus) is a reservoir of many zoonotic pathogens and lives in close proximity to humans in urban environments. Human infection with rodent-borne disease occurs either directly through contact with a rat or its excreta, or indirectly via arthropod vectors such as fleas and ticks. Here, we report on the diversity and abundance of ectoparasitic arthropod species and associated pathogenic bacteria from 133 Norway rats trapped over a 10-mo period in Manhattan, New York, NY. Norway rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 54 publications
2
42
0
Order By: Relevance
“…In contrast, many rodents host fleas which can bite other taxa and have been found to host many genotypes of Bartonella that have originated in rodents and infected other species such as humans (e.g. 32,33). Considerations of the host specificity of the vector species may be very important for determining the risk for disease spillover and indeed public health officials recommend avoidance of potential vectors as the most important measure for prevention of bartonellosis (9).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, many rodents host fleas which can bite other taxa and have been found to host many genotypes of Bartonella that have originated in rodents and infected other species such as humans (e.g. 32,33). Considerations of the host specificity of the vector species may be very important for determining the risk for disease spillover and indeed public health officials recommend avoidance of potential vectors as the most important measure for prevention of bartonellosis (9).…”
Section: Discussionmentioning
confidence: 99%
“…A study from an urban center in Southern California shows that the population of fleas on rodents and backyard wildlife has increased significantly since 1967 (Krueger et al 2016). A study of rat ectoparasites in New York City found the number of fleas on Norway rats to be higher than previously recorded (Frye et al 2015).…”
Section: Impacts To California and Californiansmentioning
confidence: 94%
“…However, little is known about the ecology of wild commensal rodents and the pathogens they can vector in urban, residential communities. Recent studies of urban commensal rodents in Vancouver and New York City, report the presence of pathogens like Leptospira and Bartonella in commensal rodent populations (Frye et al 2015, Himsworth et al 2015, McVea et al 2018). The Vancouver Rat study has found evidence of E. coli in 62.7% of urban rats tested.…”
Section: Introductionmentioning
confidence: 99%
“…The cost of parts used in the construction is relatively low (<$75) and would be much smaller if mass produced. Though, this expense, even at its most expensive point, could be justified against the overall benefit of highly-variable animal models in the research laboratory (Stryjek and Pisula, 2008), the potential for reduced risk of disease in the wild (Firth et al, 2014;Frye et al, 2015), and the billion-dollar worldwide industry of rodent control (Parsons et al, 2015).…”
Section: Placementmentioning
confidence: 99%
“…Psychologists and neuroscientists who use rat models in the laboratory or in the field, may trap wild rats, or even create new strains of outbred laboratory rats to increase variability in their study populations (Stryjek and Pisula, 2008). Epidemiologists and public health officials may trap rodents as part of surveillance programs to determine if, or when, potential pathogens are entering the population (Firth et al, 2014;Frye et al, 2015;Parsons et al, 2015Parsons et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%